Epistemologi Pesantren dan Integrasi Ilmu dalam Islam Kontemporer: Sebuah Tinjauan Literatur - Agus Nuril Anwar; Muhammad Husni (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This article aims to formulate a pesantren epistemological framework as a model for knowledge integration in contemporary Islam. The study is motivated by the fragmentation of modern knowledge, which separates revelation, scientific rationality, and spirituality, resulting in a dichotomy between religious knowledge and modern science. This research employs a qualitative approach using a literature-based method in the form of a critical literature review. The data consist of scientific journal articles indexed in SINTA and Scopus published between 2020 and 2025, focusing on pesantren epistemology, Islamic epistemology, knowledge integration, and spirituality in Islamic education. Data analysis was conducted through thematic and comparative-conceptual analysis to identify dominant patterns, conceptual strengths, and epistemological gaps in previous studies. The research results indicate that Islamic boarding school epistemology has strong epistemological potential to be developed as an integrative knowledge system. It places revelation and Islamic scientific tradition as the primary normative sources, rationality as a methodological instrument, and spirituality as the ethical and epistemic foundation in the process of knowledge production and validation. However, previous studies tend to be fragmentary and emphasize implementation aspects. This article presents a conceptual synthesis that positions Islamic boarding schools as an integrative Islamic epistemological paradigm, capable of bridging the Islamic scientific tradition, modern science, and spirituality holistically and coherently. Keywords: Contemporary Islam, Epistemology of Pesantren, Islamic Education, Knowledge Integration, Spirituality